2021
DOI: 10.1073/pnas.2013598118
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming of tumor cell–intrinsic STING function sculpts antigenicity and T cell recognition of melanoma

Abstract: Lack or loss of tumor antigenicity represents one of the key mechanisms of immune escape and resistance to T cell–based immunotherapies. Evidence suggests that activation of stimulator of interferon genes (STING) signaling in tumor cells can augment their antigenicity by triggering a type I IFN-mediated sequence of autocrine and paracrine events. Although suppression of this pathway in melanoma and other tumor types has been consistently reported, the mechanistic basis remains unclear. In this study, we asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 36 publications
5
94
0
Order By: Relevance
“…PD-1 blockade delivered together with intratumoral BO-112 achieved partial responses in some patients with primary resistance to anti-PD-1 alone [217]. However, innate interferon sensing is often epigenetically inactivated in immunogenic tumors, via hypermethylation of the promoters of cyclic GMP-AMP synthase (CGAS) and stimulator of interferon genes (STING1) genes [218]. Impaired tumor STING signaling results in impaired immunogenicity and poor response to immunotherapies [219,220].…”
Section: Immunotherapy With Anti-pd-1 Increases Mhc-i Expression On Ifnγ-sensitive Tumor Cells In the Presence Of Tumor-reactive T Cells mentioning
confidence: 99%
See 1 more Smart Citation
“…PD-1 blockade delivered together with intratumoral BO-112 achieved partial responses in some patients with primary resistance to anti-PD-1 alone [217]. However, innate interferon sensing is often epigenetically inactivated in immunogenic tumors, via hypermethylation of the promoters of cyclic GMP-AMP synthase (CGAS) and stimulator of interferon genes (STING1) genes [218]. Impaired tumor STING signaling results in impaired immunogenicity and poor response to immunotherapies [219,220].…”
Section: Immunotherapy With Anti-pd-1 Increases Mhc-i Expression On Ifnγ-sensitive Tumor Cells In the Presence Of Tumor-reactive T Cells mentioning
confidence: 99%
“…Impaired tumor STING signaling results in impaired immunogenicity and poor response to immunotherapies [219,220]. The cGAS-STING pathway sensitivity and MHC-I expression in tumor cells, as well as the resulting T-cell reactivity, could be restored by the DNMT inhibitors such as azacytidine [218]. Treatment with another DNMT inhibitor (guadecitabine) improved T-cell responses in the animal model of breast cancer via upregulation of tumor MHC-I expression and increased T-cell recruitment to the tumor [221].…”
Section: Immunotherapy With Anti-pd-1 Increases Mhc-i Expression On Ifnγ-sensitive Tumor Cells In the Presence Of Tumor-reactive T Cells mentioning
confidence: 99%
“…This is in line with previous studies indicating a majority of the melanoma and colorectal cancer cell lines analyzed have intact IFN production in response to poly IC dsRNA stimulation [ 76 , 77 ]. Recently, it has been identified that the use of demethylating agents can enhance cGAS/STING expression in silenced melanoma cell lines [ 78 ]. This reversal results in improved T lymphocyte recognition and increased IFN-γ production in an in vitro co-culture system [ 78 ].…”
Section: Tumor Susceptibility To δγ 1 345 Ohsv Replicationmentioning
confidence: 99%
“…Recently, it has been identified that the use of demethylating agents can enhance cGAS/STING expression in silenced melanoma cell lines [ 78 ]. This reversal results in improved T lymphocyte recognition and increased IFN-γ production in an in vitro co-culture system [ 78 ]. Although much less prevalent (< 1% of tumors within TCGA database), it should be noted that several missense mutants of cGAS and STING were identified in the TCGA database [ 33 ].…”
Section: Tumor Susceptibility To δγ 1 345 Ohsv Replicationmentioning
confidence: 99%
See 1 more Smart Citation